Targeted deletion of c‐Met in thymic epithelial cells leads to an autoimmune phenotype. Issue 2 (3rd December 2017) - Su, Min; Hu, Rong; Song, Yinhong; Liu, Yalan; Lai, Laijun
Abstract: Hepatocyte growth factor (HGF) and its receptor c‐Met signaling have been implicated in regulating various types of cells including epithelial cells. We have previously reported that c‐Met is expressed by thymic epithelial cells (TECs), and that in vivo administration of hybrid cytokines containing IL‐7 and the beta‐ or alpha‐chain of HGF significantly increase the number of TECs. In order to study the role of c‐Met signaling in TECs, we generated conditional knockout (cKO) mice in which c‐Met was specifically deleted in TECs using a Foxn1‐Cre transgene. We show here that c‐Met deficiency in TECs results in age‐progressive reduction in TEC number and reduced number of regulatory T cells. Consequently, c‐Met TEC cKO mice displayed an autoimmune phenotype. Thus, c‐Met signaling in TECs is important for the maintenance of TECs and immune self‐tolerance. Abstract : c‐Met deficiency in thymic epithelial cells (TECs) results in reduced number of TECs and regulatory T cells. c‐Met deficiency in TECs results in an autoimmune phenotype.